The Problem in Total Defence Implementation: The Case Study of Program Latihan Khidmat Negara (PLKN) - Hasan, Hasim; Haris Syed Mustapa, Syed Abdul; Faisol Keling, Mohamed; Iskandar Lee Abdullah, Mohamad Ainuddin (International Journal of Psychosocial Rehabilitation, 2020)
National Service Training Program (Program LatihanKhidmat Negara-PLKN) is a three months compulsory training course in all PLKN centres in Malaysia. SijilPelajaran Malaysia school leavers or aged 17 years old and above are selected to participate in this program. This program intends to strengthen self- discipline, personality and enhance the patriotism spirit among the younger generation, instil unity among races and national integration and form positive characteristics through positive values. This program is seen as a call-up as a preparation for the country in facing security threat. The government gives an impression, that with huge expenditure it intends for the security and defence which are the responsibilities that cannot be seen lightly due to other countries’ successful implementation. However, since the implementation in 2003, questions have been raised on the effectiveness of PLKN in achieving Ministry of Defence objectives and Total Defence concept. Therefore, this study looks into the problem faced in implementation of PLKN and the effect to the Total Defence concept in National Defence Policy.